2016
DOI: 10.1177/1847979016670526
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy indicators for customer retention

Abstract: It is widely known that market orientation (MO) and customer value help companies achieve sustainable sales growth over time. Nevertheless, one cannot ignore the existence of a gap on how to measure this relationship. Following this idea, this study proposes six fuzzy key performance indicators that aims to measure customer retention and loyalty of the portfolio. The work uses 300 sales executives. This exploratory study concludes that indicators such as MO, customer orientation (CO), degree of CO value of sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…For agricultural analysis [45], engineering [46,49]. In social sciences, [47] analyze the level of customer retention with to put diffuse indicators; [9] proposes Multidimensional Fuzzy Indicator in Quality of work (QoW) analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For agricultural analysis [45], engineering [46,49]. In social sciences, [47] analyze the level of customer retention with to put diffuse indicators; [9] proposes Multidimensional Fuzzy Indicator in Quality of work (QoW) analysis.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous research, the following relevant authors establish the following regarding the key performance indicators: [11] proposes a process-based performance measurement framework (PPMF); [12] proposes a fuzzy KPY in customer retention; [59] proposes KPY through fuzzy customer experience by free text; [28] defines how performance indicators in higher education applies to the assessment of doctoral/research degrees; [44] proposes a KPY by fuzzy linguistic variables to incentivize a pay system; and [58].…”
Section: Introductionmentioning
confidence: 99%
“…It is more appropriate for expressing the logical relations related to human expression. 23,24 Nevertheless, Velasquez 25 showed that providing an exact value of the degree of membership for an element may be difficult; there may be a hesitation degree between the membership and nonmembership. A decision maker (DM) may express his/her opinion, while he/she is not so sure about it.…”
Section: Introductionmentioning
confidence: 99%